The electrical properties of a planar coil electromagnetic acoustic transducer and their implications for noise performance. (18th December 2015) - Seher, Matthias; Challis, Richard
Abstract: This paper is concerned with the electrical properties of an electromagnetic acoustic transducer (EMAT) formed of a flat spiral coil coupled to steel sheet components and operating over a narrow band of frequencies around 50 kHz, well below significant resonances. The electromagnetic skin effect is a significant contributor to the terminal impedance of the EMAT and hence to signal sensitivity, Johnson noise generation and the achievable signal-to-noise ratios (SNR). A transformer model is developed to simulate these effects and to assist in the optimization of the SNR. In this analysis Johnson noise in the system is compared to the unknown emf generated in the eddy current path by an incident acoustic wave to yield a fundamental SNR. The attainable SNR of the whole system is normalized to this in the form of a noise figure.